Physiological role of Kvβ2 (AKR6) in murine skeletal muscle growth and regulation - Chapalamadugu, Kalyan C. (Acta Physiol (Oxf), 2018)
AIM: Potassium channel accessory subunits (Kvβ) play a key role in cardiac electrical activity through ion channel modulation. In the present study we hypothesize that Kvβ2 regulates skeletal muscle growth and fiber phenotype via protein-protein interactions. METHODS: Kvβ2 knockout mouse model was used for morphometric, immunohistochemical and biochemical analysis to evaluate the role of Kvβ2 in skeletal muscle physiology. RESULTS: Deletion of Kvβ2 gene in mice (Kvβ2 knockout, KO) leads to significant decrease in body weight along with skeletal muscle size. Key hind limb muscles such as biceps, soleus, and gastrocnemius were significantly smaller in size in KO mice compared to that of wild type. Morphometric measurements and histological analysis clearly point that the fiber size is decreased in each of the muscle type in KO compared with wild type mice. In addition, Kvβ2 deletion contributes to fiber type switching from fast to slow fiber as indicated by more abundant MHCI expressing fibers in gastrocnemius and soleus muscles, which may underscore the smaller muscle size alongside increase in U3 ubiquitin ligase;NEDD4 expression. Using targeted siRNA knockdown approach, we identified that Kvβ2 knockdown do not affect the myoblasts proliferation. However, Pax7 expression was significantly decreased in 4 week old gastrocnemius muscle suggesting that cellular reserve for growth may be deficient in KO mice. This is further supported by decreased migratory capacity of C2C12 cells upon siRNA targeted Kvβ2 knockdown. CONCLUSION: Overall, this is the first report identifying that genetic deletion of Kvβ2 leads to decreased skeletal muscle size along with isotype switching.